2010
DOI: 10.1186/1477-5956-8-37
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins related to the stress response in Enterococcus faecalis V583 caused by bovine bile

Abstract: BackgroundEnterococcus faecalis is an opportunistic pathogen and one of the most important causes of hospital infections. Bile acids are a major stress factor bacteria have to cope with in order to colonize and survive in the gastro-intestinal tract. The aim of this study was to investigate the effects of bile acids on the intracellular proteome of E. faecalis V583.ResultsThe proteomes of cells challenged with 1% bile were analyzed after 20 - 120 minutes exposure, using 2D gel electrophoresis and mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 42 publications
2
22
0
1
Order By: Relevance
“…Previous research has demonstrated that environmental stressors induce transcription of multiple genes, and these genes are often similar across different stressors and different species of bacteria [11]. We compared genes found to be differentially expressed in this study to genes associated with stress response more generally in E. faecalis [22,[48][49][50][51][52][53] as well as other bacteria [11,23,24,[54][55][56]. The recombinase A gene, recA, is involved in homologous recombination, DNA repair, and known to be an important part of bacterial stress response.…”
Section: Differential Expression Of Genes Involved In Bacterial Stresmentioning
confidence: 94%
“…Previous research has demonstrated that environmental stressors induce transcription of multiple genes, and these genes are often similar across different stressors and different species of bacteria [11]. We compared genes found to be differentially expressed in this study to genes associated with stress response more generally in E. faecalis [22,[48][49][50][51][52][53] as well as other bacteria [11,23,24,[54][55][56]. The recombinase A gene, recA, is involved in homologous recombination, DNA repair, and known to be an important part of bacterial stress response.…”
Section: Differential Expression Of Genes Involved In Bacterial Stresmentioning
confidence: 94%
“…Protein separation, gel analysis, trypsin treatment, and extraction of proteins of interest were performed as described previously (1). The gels were scanned and analyzed by Delta2D software (Decodon, Greifswald, Germany) and by a pixel-based analysis of multiple images for the identification of proteome patterns of two-dimensional (2D) gel electrophoresis images (6).…”
Section: Methodsmentioning
confidence: 99%
“…Many efflux pumps are also linked to drug resistance (10). Studies with E. faecalis have shown that this organism alters gene expression and protein synthesis when grown in the presence of bile (11,12), and resistance to bile stress also provides cross-protection against other sources of stress (13). However, the exact mechanisms for enterococci's resistance to bile stress have not been completely elucidated.…”
mentioning
confidence: 99%